2019
DOI: 10.1038/s41597-019-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban link travel speed dataset from a megacity road network

Abstract: Link travel speeds in road networks are fundamental data in many research areas of traffic, transportation, and logistics. To support the research in these areas, we develop a dataset, containing the travel speeds on each road link and in different time periods together with the real road network map. The dataset is collected from a representative megacity in Western China, Chengdu. The road network of this city involves different urban road network structures. The dataset shows the realistic variations and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…Then, the stability level of the S scenarios is calculated using the stability test proposed by Guo et al [27] to determine the number of stochastic scenarios required. The processes for calculating the stability level of S scenarios are shown as follows: generate 2m + 1 scenario sets that have S − m, S − m + 1, .…”
Section: Experimental Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the stability level of the S scenarios is calculated using the stability test proposed by Guo et al [27] to determine the number of stochastic scenarios required. The processes for calculating the stability level of S scenarios are shown as follows: generate 2m + 1 scenario sets that have S − m, S − m + 1, .…”
Section: Experimental Settingsmentioning
confidence: 99%
“…Modeling the stochasticity and correlation of link travel speeds in real road networks is highly complicated because there are very high-dimensional dependent random vector [27]. For example, a stochastic time-dependent road network with 200 road links and 10 time periods implies 2000 random speed variables and 1,999,000 (2000 × 1999 ÷ 2) distinct correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Link travel speeds in road networks are fundamental for a variety of decision-making problems in logistics, transportation and traffic 7 . Link travel speeds change over space and time due to such as changing travel demands and unstable traffic flows.…”
Section: Introductionmentioning
confidence: 99%
“…By examining the correlations of immediately neighboring links in space and time based on a 45-day travel speed dataset, significant spatial correlations were observed for about 50% of the links and their adjacent links in the same direction, while travel speeds between two consecutive time periods exhibited strong significant temporal correlations 7 . By investigating temporal correlations and spatial correlations of 30 randomly chosen links from the California freeway network based on a 102-day travel speed dataset 17 , it is found that, the temporal correlation of travel speeds on one link decreases on the whole with the increase of time period lag.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation